Research progress on arsenic, arsenic-containing medicinal materials, and arsenic-containing preparations: clinical application, pharmacological effects, and toxicity - Yang, Yichu; Li, Yiye; Li, Ran; Wang, Zhang (Frontiers in Pharmacology, 2024)
Introduction: The toxicity of arsenic is widely recognized globally, mainly harming human health by polluting water, soil, and food. However, its formulations can also be used for the clinical treatment of diseases such as leukemia and tumors. Arsenic has been used as a drug in China for over 2,400 years, with examples such as the arsenic-containing drug realgar mentioned in Shennong’s Herbal Classic. We have reviewed references on arsenic over the past thirty years and found that research has mainly focused on clinical, pharmacological, and toxicological aspects. Results and Discussion: The finding showed that in clinical practice, arsenic trioxide is mainly used in combination with all-trans retinoic acid (ATRA) at a dose of 10 mg/d for the treatment of acute promyelocytic leukemia (APL); realgar can be used to treat acute promyelocytic leukemia, myelodysplastic syndrome, and lymphoma. In terms of pharmacology, arsenic mainly exerts anti-tumor effects. The dosage range of the action is 0.01–80 μmol/L, and the concentration of arsenic in most studies does not exceed 20 μmol/L. The pharmacological effects of realgar include antiviral activity, inhibition of overactivated lactate dehydrogenase, and resistance to malaria parasites. In terms of toxicity, arsenic is toxic to multiple systems in a dose-dependent manner. For example, 5 μmol/L sodium arsenite can induce liver oxidative damage and promote the expression of pro-inflammatory factors, and 15 μmol/L sodium arsenite induces myocardial injury; when the concentration is higher, it is more likely to cause toxic damage.